Islamic Education as a Response to National and Global Social Issues: Disciplinary and Interdisciplinary Perspectives - Hakim, Arif Rahman; Ruswandi, Uus; Erihadiana, Mohamad (Universitas Sang Bumi Ruwa Jurai, 2025)
This study explores the role of Islamic education in addressing pressing national and global social issues through disciplinary and interdisciplinary research approaches. Amid rising social inequality, radicalization, moral decline, and intercultural tensions, Islamic education offers transformative potential grounded in core values such as justice (‘adl), compassion (rahmah), and public benefit (maslahah). The urgency of these challenges in today’s interconnected and pluralistic society necessitates renewed efforts to integrate Islamic educational values with contemporary solutions. Using a qualitative library research method and content analysis of primary and secondary sources, the study reveals that a disciplinary approach rooted in Islamic sciences like tafsir, hadith, fiqh, and ‘aqidah preserves identity and offers normative responses to social issues. In contrast, an interdisciplinary approach enables the blending of Islamic thought with modern fields such as sociology, psychology, and economics, facilitating the creation of curricula responsive to current realities. Integrating these perspectives within a multidisciplinary framework enhances the practical relevance and holistic nature of Islamic education. The study concludes that combining both approaches strengthens Islamic education’s role as a proactive force for social transformation. It recommends that policymakers and educational institutions implement integrative curricula that connect Islamic values with interdisciplinary insights to meet the complex demands of contemporary society.